(untitled) (Bangladesh Journal of Medical Science, 2014)
Background: Obturators are used to separate the oro-nasal opening. These improve speech and other oral functions as well as provide psychological support to the patients. Adding radicular attachments in an obturator makes more effective. Objective: To evaluate and compare the effectiveness of obturator with radicular attachment and conventional obturator in articulation of speech. Materials and Methods: Fifty patients, age ranged from 18 to 72 years, with maxillectomy defect were selected as the sample of the study. Among them 25 patients were treated with obturator with radicular attachment and another 25 patients were treated with conventional obturator. After insertion of obturator, data were collected on the basis of articulation of speech. Results: Patients treated with obturator with radicular attachment showed significantly better (P value <0.001) articulation of speech. Conclusion: Obturator with radicular attachment is more effective than conventional obturator. DOI: http://dx.doi.org/10.3329/bjms.v13i3.19152 Bangladesh Journal of Medical Science Vol.13(3) 2014 p.298-301